Electroluminescent properties of Tb-doped carbon-enriched silicon oxide - Tiagulskyi, S.I.; Nazarov, A.N.; Gordienk, S.O.; Vasin, A.V.; Rusavsky, A.V.; Nazarova, T.M.; Gomeniuk, Yu.V.; Rudko, G.V.; Lysenko, V.S.; Rebohle, L.; Voelskow, M.; Skorupa, W.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
An electroluminescent device utilizing a heterostructure of amorphous terbium doped carbon-rich SiOx (a - SiOx : C : Tb) on silicon has been developed. The a - SiOx : C : Tb active layer was formed by RF magnetron sputtering of a - SiO₁₋x : Cx : H(:Tb) film followed by high-temperature oxidation. It was shown that, depending on the polarity of the applied voltage, the electroluminescence is either green or white, which can be attributed to different mechanisms of current transport through the oxide film – space charge limited bipolar double injection current for green electroluminescence and trap assisted tunneling or Fowler-Nordheim tunneling for white electroluminescence.